Barriers to women's collective identity formation in contaminated communities. Issue 4 (2nd October 2022) - Longest, Landen; Adams, Alison E.; Shriver, Thomas E.
ABSTRACT: Extant research emphasizes the resonance of gendered collective identities in mobilizing women's environmental activism, particularly around motherhood and caregiving. Gaps remain, though, in our understanding of the specific barriers that can obstruct the formation of collective identity among groups of women who share environmental concerns. To interrogate this issue, we explore the case of two cancer clusters in North Carolina that many residents suspect are related to coal ash contamination. We use qualitative interviews with women affected by the clusters (n = 36) to identify factors that have inhibited the formation of a mobilizing collective identity. Our results suggest that the reciprocal relationship between disempowerment and isolation, as well as the compounding burdens of emotional and care labor associated with managing environmental illness, prevented the formation of a collective identity in this case. These findings highlight how factors particular to cases of environmental illness can forestall, rather than drive, women's environmental activism.